Bioluminescence Imaging to Track Bacteroides fragilis Inhibition of Vibrio parahaemolyticus Infection in Mice - Li, Zhengchao; Deng, Huimin; Zhou, Yazhou; Tan, Yafang; Wang, Xiaoyi; Han, Yanping; Liu, Yangyang; Wang, Ye; Yang, Ruifu; Bi, Yujing; Zhi, Fachao (Frontiers in Cellular and Infection Microbiology, 2017)
Bacteroides fragilis is an anaerobic, Gram-negative, commensal bacterium of the human gut. It plays an important role in promoting the maturation of the immune system, as well as suppressing abnormal inflammation. Many recent studies have focused on the relationship between B. fragilis and human immunity, and indicate that B. fragilis has many useful probiotic effects. As inhibition of intestinal pathogens is an important characteristic of probiotic strains, this study examined whether B. fragilis could inhibit pathogenic bacteria. Results showed that Vibrio parahaemolyticus was inhibited by B. fragilis in vitro, and that B. fragilis could protect both RAW 264.7 and LoVo cells from damage caused by V. parahaemolyticus. Using in vivo imaging, we constructed a light-emitting V. parahaemolyticus strain and showed that B. fragilis might shorten the colonization time and reduce the number of lux-expressing bacteria in a mouse model. These results provide useful information for developing B. fragilis into a probiotic product, and also indicate that this commensal bacterium might aid in the clinical treatment of gastroenteritis caused by V. parahaemolyticus.